Determination total antocyanin in brown rice (Oryza bicara) - Vina Juliana Anggraeni; Liska Ramdanawati; Winda Ayuantika (Jurnal Kartika Kimia, 2018)
Brown rice contains anthocyanin compounds. Antosianin is a natural pigment that gives red color to brown rice. Anthocyanin is an unstable compound, so it is necessary to optimize the extraction method to find out the proper extraction method in obtaining the largest anthocyanin level in brown rice. Optimization of extraction conducted in this study include, solvent, addition of HCl and size of brown rice Measurement of levels in this study using the method of differential pH with visible spectrofotometer tool. Determination of levels that have been done obtained anthocyanin levels on samples of fine methanol rice, intact methanol, 1% HCl 1% methanol and 1% HCl 1% respectively are 0.0591 (mg / 100g), 0.0551 (mg / 100g), 0.1503 (mg / 100g), and 0.1212 (mg / 100g) respectively, . The results obtained by the fine rice samples dissolved with 1% HCl methanol had the highest anthocyanin levels.